2020
DOI: 10.24018/ejgeo.2020.1.5.58
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Noise Pollution in the Major Traffic Intersections of Khulna Metropolitan City in Bangladesh and its Possible Effect on Noise-Exposed People

Abstract: This study was conducted in the Khulna metropolitan city to determine the status of noise pollution at major traffic intersections and assess the possible effect of noise on regular noise afflicted people. For this research, five busiest roadways and traffic intersections; two mixed zone and three commercial zones were selected purposively and 'ST-8850 Sound Level Meter' was used to record the noise pressure level. Average noise pressure level and some noise parameters (Leq, L10, L50, L90, and Lnp) were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Atmospheric pollution is not only limited to physical particulate matter but also includes the transmission of sound and noise in the city (Brisman et al 2021;García Ruiz and South 2018). Numerous megaprojects across Bangladesh involve transportation and construction works, which increases noise pollution (Akhand et al 2012;Sultana et al 2020). Dhaka city is particularly exposed (Chowdhury et al 2010), but almost every town and city in Bangladesh suffers severe sound pollution (Dey 2002) as a result of traffic congestion (e.g., the frequent use of sirens and horns), construction sites, music and public announcement sound systems, places of prayer and public meetings (Keegan 2018;Mansoor 2020).…”
Section: Noise Pollutionmentioning
confidence: 99%
“…Atmospheric pollution is not only limited to physical particulate matter but also includes the transmission of sound and noise in the city (Brisman et al 2021;García Ruiz and South 2018). Numerous megaprojects across Bangladesh involve transportation and construction works, which increases noise pollution (Akhand et al 2012;Sultana et al 2020). Dhaka city is particularly exposed (Chowdhury et al 2010), but almost every town and city in Bangladesh suffers severe sound pollution (Dey 2002) as a result of traffic congestion (e.g., the frequent use of sirens and horns), construction sites, music and public announcement sound systems, places of prayer and public meetings (Keegan 2018;Mansoor 2020).…”
Section: Noise Pollutionmentioning
confidence: 99%
“…They also found that noise levels of the study areas were also higher compared to the standard noise levels. The status of noise pollution at the major intersections in the Khulna metropolitan city was assessed by Sultana et al (2020). It was reported that noise levels in diverse areas were higher than in commercial areas.…”
Section: Parvinmentioning
confidence: 99%
“…There are some research works on sound pollution, especially in the main noisy traffic points of the metropolitan area (Oguntunde et al, 2019;Sultana et al, 2020;Uddin et al, 2018). Many factors contribute to higher sound levels.…”
Section: Introductionmentioning
confidence: 99%
“…Immeasurable people in Bangladesh face several health risks due to sound pollution. Recent studies have shown that noise levels are higher at different points in the city center of Magura (Das et al, 2018), Chittagong (Uddin et al, 2018), Sylhet (Das and Basak, 2020), Khulna (Sultana et al, 2020), Mymensingh (Hasan et al, 2021), and Dhaka (Parvin, 2021). It is becoming an unreasonable intervention to slowly but surely impose human well-being, health (physical and psychological), and quality of life (Islam et al, 2015;Masoudzadeh et al, 2017, Oguntunde et al, 2019Sultana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation